EFEKTIVITAS METODE PEMBELAJARAN PROBLEM POSING BERSETTING ADVANCE ORGANIZER PADA MATERI REAKSI REDOKS TERHADAP HASIL BELAJAR SISWA KELAS X SMA NEGERI 3 PONTIANAK - Ragil Triani; Muhamad Agus Wibowo; Raudhatul Fadhilah (Universitas Muhammadiyah Pontianak, 2017)
ABSTRAK This research had the purpose to find out the difference between students’ learning outcomes which were taught using learning problem posing method set in advance organizer and lecture method as well as to know how large the effect problem posing set in advance organizer on students’ learning outcomes in class X of SMA Negeri 3 Pontianak on redox reactions. This research was Quasi Experimental Nonequivalent Control Group design. The sampling system was purposive sampling, based on the sampling technique, X F was choosen as control class and X I was choosen as experimental class. The technique of data collection used measurement, direct communication, and direct observation techniques. The result of data analysis showed the mean score of pretest-posttest in experimental class (88,37) was higher compared to control class (69,6). According to the statistical analysis of U-Mann witney test on posttest score (α= 0,05), it was obtained the Pvalue which was 0,000 which mean that there was difference between the ability of learning outcomes in experimental and control class. The calculation using effect size showed ES=0,72 which meant problems posing set in advance organizer effected students’ learning outcomes which was 26,42%. Learning problem posing method set in advance organizer had medium effect on students’ learning outcomes.Keywords: advance organizer, learning outcome, problem posing, redox reactions